2016
DOI: 10.18039/ajesi.18656
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Özyeterlik İnançları ve Teknolojik Araç-Gereç Kullanımına Yönelik Tutumları: Balıkesir İli Örneği

Abstract: Bu araştırmanın amacı, okul öncesi öğretmenlerinin özyeterlik inançları ile teknolojik araç-gereç kullanımına yönelik tutumları arasındaki ilişkiyi ortaya koymaktır. İlişkisel tarama modelindeki araştırmanın çalışma grubu Balıkesir ilindeki bağımsız anaokullarında görev yapan 174 okul öncesi öğretmeninden oluşmaktadır. Araştırmanın verileri kişisel bilgi formu, "Okul öncesi öğretmenlerinin özyeterlik inançları ölçeği" ve "Okul öncesi eğitimde teknolojik araç-gereç kullanımına yönelik tutum ölçeği" ile toplanmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Gökmen et al (2016) revealed that teachers' self-efficacy belief levels increased as their professional experience increased. Conversely, there are studies indicating that there is no difference in the self-efficacy levels of teachers by seniority (Gömleksiz & Serhatlıoğlu, 2013;Yılmaz et al, 2016). In their study examining preschool teachers' self-efficacy belief, Guo et al (2010) reported a decrease in self-efficacy belief levels as professional experience increased.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Gökmen et al (2016) revealed that teachers' self-efficacy belief levels increased as their professional experience increased. Conversely, there are studies indicating that there is no difference in the self-efficacy levels of teachers by seniority (Gömleksiz & Serhatlıoğlu, 2013;Yılmaz et al, 2016). In their study examining preschool teachers' self-efficacy belief, Guo et al (2010) reported a decrease in self-efficacy belief levels as professional experience increased.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 95%
“…In this context, self-efficacy belief is also the source of personal development and change that will enable the teacher to have the necessary qualities (Gömleksiz & Serhatlıoğlu, 2013). Concurrently, self-efficacy belief level is effective in increasing motivation (Shunk, 1991) and in achieving success (Yılmaz, Tomris, & Kurt, 2016). Therefore, self-efficacy belief level will be effective on the negative or positive attitudes of the individual towards a certain field (Şenol & Ergün, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation can be explained by the similarity of the characteristics of the pedagogical education given in both types of schools, and the studies (Pistav Akmese and Kayhan, 2016;Ozder, Isiktas, Iskifoglu and Erdogan, 2014;Toran and Gencgel, 2016;Yilmaz, Tomris and Kurt, 2016) revealed that the school types do not make any difference in the effectiveness of teachers' class management, teaching strategies and student engagement, and similarly, it was not found to be significant on the teacher's self-efficacy beliefs. Teacher self-efficacy beliefs change related to undergraduate programs, and the result was in favour of child development teacher and preschool teacher graduates.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, it is of utmost importance that both the learners and the teachers can carry out the process effectively. The self-efficacy belief of the teacher, who conducts the learning process, determines the teacher's performance in the learning process (Pistav Akmese and Kayhan, 2016), the teaching methods and techniques he uses, classroom management (Kadim, 2012;Yilmaz, Tomris and Kurt, 2016), teacher interaction with students, relationship with colleagues as well as the families of the students in the institution teacher works for (Hoy and Spero, 2005;Kesicioglu and Guven, 2014;Siwatu, Chesnut, Alejandro and Young, 2016). The researches carried out indicate that the teachers' self-efficacy belief is affected by the teachers' amount of time spent in the teaching profession , economic satisfaction, level of education, number of students in the classroom, region where the school is located, socioeconomic status of the group they work in, educational equipment in classroom and social, cultural and economic conditions (Eells, 2011;Milner and Hoy, 2003;Ozder, 2011;Tschannen-Moran and Hoy, 2007;Tschannen-Moran and Gareis, 2004).…”
Section: Introductionmentioning
confidence: 99%